2017
DOI: 10.1103/physrevb.95.134422
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase diagram and electronic structure of UPt2Si2 at high magnetic fields: A possible field-induced Lifshitz transition

Abstract: We have measured the Hall effect, magnetotransport, and magnetostriction on the field-induced phases of single-crystalline UPt 2 Si 2 in magnetic fields up to 60 T at temperatures down to 50 mK, firmly establishing the phase diagram for magnetic fields B a and c axes. Moreover, for the B c axis we observe strong changes in the Hall effect at the phase boundaries. From a comparison to band structure calculations utilizing the concept of a dual nature of the uranium 5f electrons, we propose that these represent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In practice, this introduces disorder, which always complicates the understanding of the observed behaviour. Magnetic field enables clean tuning by changing band energies for opposite spins through the Zeeman term, and has been used to good effect in the study of a number of systems [11][12][13][14][15][16]. However, unless the intrinsic bandwidths are already very small, large fields are required to reach Lifshitz transitions, and magnetic fields also couple either constructively or destructively to many forms of order.…”
mentioning
confidence: 99%
“…In practice, this introduces disorder, which always complicates the understanding of the observed behaviour. Magnetic field enables clean tuning by changing band energies for opposite spins through the Zeeman term, and has been used to good effect in the study of a number of systems [11][12][13][14][15][16]. However, unless the intrinsic bandwidths are already very small, large fields are required to reach Lifshitz transitions, and magnetic fields also couple either constructively or destructively to many forms of order.…”
mentioning
confidence: 99%
“…Particular attention has been devoted to the crystal and magnetic structures. [6][7][8][9][10][11][12] UPt 2 Si 2 orders antiferromagnetically (AF) below T N that is reported to range between 32 K and 35 K. [7,10] It has been reported that the low-temperature AF structure is collinear with U moments of 1.9 -2.5 µ B , depending on a study, [7,10] pointing along the c-axis direction. It can be described as a (up-down) stacking of ferromagnetic uranium sheets alternating along the tetragonal axis direction.…”
Section: Introductionmentioning
confidence: 99%
“…[1,[6][7][8][9][10] The field transition has been in-terpreted as a topological Lifshitz transition. [11] Much attention has been paid to a possible crystallographic disorder [10] that has been linked to irreversibility in magnetic behavior. [12] Neutron powder and single crystal diffraction experiments have indicated that the one of the two Pt and Si atomic positions exhibit anomalously large displacement parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Sensing of magnetostriction with single mode SiO 2 FBGs in pulsed magnetic fields is successfully utilized at the National High Magnetic Field Laboratory (NHMFL) with a resolution as good as a few parts per hundred million ( ΔL/L ≈ 10 −8 ) in the best cases. This capability allows for the study of a variety of insulating and metallic condensed matter systems including geometrically frustrated magnets, quantum magnets, multiferroics, and uranium- and cerium-based antiferromagnets [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. Figure 1 shows an example of magnetoelastic effects in pulsed magnetic fields to 60 T at cryogenic temperatures on a sample of uranium dioxide (UO 2 ), which is the most commonly used nuclear fuel.…”
Section: Introductionmentioning
confidence: 99%